1998
DOI: 10.1530/eje.0.1390314
|View full text |Cite
|
Sign up to set email alerts
|

Serial analysis of the effects of methimazole or radical therapy on circulating CD16/56 subpopulations in Graves' disease

Abstract: The distribution of peripheral blood CD16/56 cytotoxic T and natural killer (NK) cells in Graves' disease patients is analyzed in order to correlate them with disease activity and with prognosis. Eighteen patients with Graves' disease, twenty-four patients with Hashimoto's thyroiditis and thirtytwo sex-and age-matched healthy control subjects were studied. Peripheral blood CD16/56 (cytotoxic T and NK) cells were analyzed by cytofluorometry. A decreased proportion of CD16/56þ and CD16/ 56þCD3þ cells were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
1
7
0
2
Order By: Relevance
“…Our findings are in agreement with the studies of Rojano et al (5), although they observed that the percentages of CD16/56 cell populations after thyrostatic therapy were still lower in comparison with healthy control subjects. In addition, the authors underlined the role of these subpopulations of cells as a prognostic marker of GD.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our findings are in agreement with the studies of Rojano et al (5), although they observed that the percentages of CD16/56 cell populations after thyrostatic therapy were still lower in comparison with healthy control subjects. In addition, the authors underlined the role of these subpopulations of cells as a prognostic marker of GD.…”
Section: Discussionsupporting
confidence: 94%
“…Graves' disease (GD) is an autoimmune thyroid disease (AITD) characterized by the production of thyroid autoantibodies against the TSH receptor, symporter Na ϩ / Ϫ , thyroglobulin or thyroperoxidase antigen, and lymphocytic infiltration of the thyroid gland (1,2). The immune cells [lymphocytes ␥␦ T-cell receptor (TCR), CD16/56(CD3ϩ), and natural killer (NK) cells] may play a pivotal role in the development of AITD (3)(4)(5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…About 5% of patients treated with antithyroid compounds have liver (Woeber, 2002;Casallo Blanco et al, 2007), lung (Tsai et al, 2001) or renal damage (Calañas-Continente et al, 2005). Also, there are other extrathyroid actions of these drugs that involve the immunological system (Gessl and Waldhausl, 1998;Rojano et al, 1998;Wang et al, 2003). Hypothyroidism has been described as having two opposing effects of oxidative stress and cell damage.…”
Section: Introductionmentioning
confidence: 99%
“…Vários outros estudos apontam o hipotireoidismo como complicação freqüente nos tratamentos antineoplásicos como a radioterapia em pacientes com neoplasia de cabeça e pescoço ou com o uso de Interleucina-2 e Interferon alfa-2 no tratamento de tipos câncer, entre eles o melanoma (DORVAL et al, 1992;KRUIT et al, 1991;MINI et al, 2001;MÖNIG;HAUSCHILD;LANGE;FÖLSCH, 1994;ROSE et al, 1999 Experimento 1 -crescimento local e sobrevida:…”
unclassified